Privacy Protection Policy for Big Data Analytics in the Malaysian Telecommunications Sector - Hui Na Chua; Younghoon Chang; Siew Fan Wong; Chor Min Tan (International Telecommunications Society (ITS), 2015)
The telecommunications sector has accessed to large amount of data. When use effectively, this Big Data enables the telcos to achieve efficiency and profitability across the entire telecommunications value chain. However, the potential advantage of Big Data may be tempered by increasing privacy concern among users. Countries across different parts of the world including Malaysia have enacted data protection policy. In Malaysia, the Personal Data Protection Act 2010 (PDPA) was officially enforced on November 15th, 2013. To date, its implementation remains challenging and its effect is unclear. This paper attempts to understand the state of data protection policy implementation and its challenges from the viewpoints of three major stakeholders: the users (i.e., the data owners and creators), the telcos (i.e., the data recipients), and the government (i.e., the policy enforcer). Guided by Giddens' Structuration Theory and the Competing Value Framework, semi-structure interview data will be collected from the three stakeholders to understand how differing perspectives of the stakeholders shape the data protection structure/institution and vice versa.
Keywords: 330; Privacy protection policy; big data analytics; telecommunications sector; fair information practices; privacy concerns